Multi-organ benign and malignant tumors: recognizing Cowden syndrome: a case report and review of the literature - Gosein, Maria Angela (BMC Res Notes, 2016)
BACKGROUND: Cowden syndrome is an autosomal dominant disorder with a predisposition to multiple benign and malignant tumors. In our patient, in addition to breast and endometrial malignancies as well as facial trichilemmomas, she was noted to have multiple meningiomas, pancreatic lipomas and lung cysts. These latter lesions have been noted in previous Cowden syndrome case reports, but are not included in the diagnostic criteria at this time. To our knowledge, this is the first case of multiple meningiomas in this syndrome. Further studies are therefore warranted to assess the significance of these findings in Cowden syndrome. CASE PRESENTATION: A middle-aged Afro-Caribbean known endometrial carcinoma patient (post surgery and adjuvant radiotherapy), presented with a locally advanced breast carcinoma. She received neoadjuvant chemotherapy followed by a modified radical mastectomy and axillary lymph node clearance. Her past medical history included a sphenoid wing meningioma for which she received definitive external beam radiotherapy. She was also known to have a multinodular goiter, anal polyp and longstanding mucocutaneous lesions. Further workup revealed additional smaller meningiomas, a parotid arteriovenous malformation, a lung cyst and pancreatic lipomas. Overall, consortium criteria were met for the diagnosis of Cowden syndrome. Furthermore, genetic testing identified a pathogenic mutation in the PTEN gene. She will be closely followed with annual clinical examination, dermatologic assessment and screening colonoscopies. She will perform interval whole body contrast enhanced CT for continued surveillance for metastatic disease. CONCLUSION: Cowden syndrome is likely to be an under diagnosed condition, but critically important to identify due to its cancer predisposition. When encountering multi-organ tumors, diagnostic criteria for Cowden syndrome should be sought in order to increase the diagnostic rates. Cancer surveillance for carcinoma detection in the early and curative stages remains the most critical aspect of management.